Pengaruh Kemampuan Menyusun Laporan Keuangan, Literasi Keuangan Dan Penggunaan Teknologi Informasi Terhadap Kinerja UMKM - Monica Dewi Ilarrahmah; Susanti - - (Universitas Hamzanwadi, 2021)
One of the ways to improve people’s welfare can be done by improving the performance of small and medium scale bussinesses because MSMEs is a place for most people to fulfill their daily needs. This reaserch was conducted with the aim pf knowing whether the ability to compile financial reports, financial literacy and the use of infrmation technology can have an influence on the performace of MSMEs. This Research is classified as a quantitative research by utilizing data obtained from 100 respondents consisting of MSMEss Players. The data collection stage was carried out with instruments in the form of questionnaires and test. The classical assumption test uses the normality test, multicolonierity and heteroscedasticity. The Analytical method used is descriptive analysis and inferential analysis, including multile linear regression comparison analysis. The research that has been carried put has resulted in (1) the abily to compile financial reports, financial literacy and the use of information technology jointly influene the performance of MSMEs in Babat distrct. (2) the ability to compile financial statements has a positive and significant effect is 0.006. (3) financial literacy has a positive effect with significance is 0.000. (4) the use of information technology has a positive effect with a significance is 0.000